The Avengers, Earth's mightiest heroes. Volume 1, Heroes assemble! [videorecording (DVD)] - Bloom, Brian, 1970-; Loomis, Eric, 1964-; Mathis, James C.; Cox, Chris; O'Shaughnessey, Colleen (Marvel DVD super hero collection., 2011)
If the planet is threatened by super villains, time traveling conquerors, alien invaders, mythical beasts, or robots bent on the total destruction of humanity, if the forces of evil are so overwhelming that no single hero has the power to save the world, when there is no hope left, you assemble the AVENGERS. The Avengers are the best of the best in the Marvel universe, the greatest heroes who take on the unbeatable foes.